Consensus Control of Multi-Hopping-Rover Systems: Convergence Analysis - Shuntaro Takekuma; Shun-Ichi Azuma; Ryo Ariizumi; Toru Asai (IEEE Access, 2023)
A hopping rover is a mobile robot developed for exploring low-gravity planets. The movement is based on hopping motion for moving on rough ground in low gravity. For efficient exploration, it is desirable to construct a cooperative system with multiple rovers. Such a system is called here the multi-hopping-rover systems. This paper addresses a consensus control problem for the multi-hopping-rover systems, where the hopping rovers involve uncertain dynamics caused by hopping motion. By representing the dynamics by a stochastic model and focusing on the dynamics of the disagreement, we present a condition on the control gain so that the system converges to consensus in a mean-square sense. The result is demonstrated by numerical simulation.